Risk factors for intracardiac thrombus in peripartum cardiomyopathy: a retrospective study in China. (21st September 2022) - Fu, Kang; Zhang, Hui; Chen, Naiyi; Hu, Yue; Xiao, Jie; Zhang, Xinyu; Lin, Zongwei; Lu, Huixia; Ji, Xiaoping
Abstract: Aims: Peripartum cardiomyopathy (PPCM) are more vulnerable to intracardiac thrombus than other types of cardiomyopathies, although explicit anticoagulant strategy is not sure. Too aggressive anticoagulation therapy can lead to severe bleeding events. Hence, we want to construct a risk stratification model for intracardiac thrombus in PPCM patients. Methods and results: A total of 159 suspected PPCM cases were initially screened, whereas 123 confirmed cases were enrolled in the final analysis. The study population was randomly assigned as derivation group ( N  = 83) and validation group ( N  = 40). The derivation cohort was utilized to develop the model, and the validation cohort was used to internal validate the discriminatory ability of the model. Formation of intracardiac thrombus was detected in 22 patients. After adjusted by multivariable logistic regression analysis, left ventricle ejection fraction (LVEF, OR 0.772, 95% CI 0.665–0.897, P  = 0.001), haemoglobin levels (OR 1.050, 95% CI 1.003–1.099, P = 0.038), and thrombocyte counts (OR 1.018, 95% CI 1.006–1.029, P  = 0.003) were identified as risk factors independently associated with intracardiac thrombus and were finally included in the tentative risk stratification model with a C‐indexes of 0.916 (95% CI: 0.850–0.982, P  < 0.001). A score of ≤7 was regarded as low risk, 8–10 defined intermediate risk, and ≥11 defined high risk in our model. Internal validation showed good discriminatory ability of the model with a C‐indexes of 0.790 (95% CI: 0.644–0.936, P  = 0.017). Conclusions: In our retrospective study, impaired LVEF, elevated haemoglobin levels, and high thrombocyte counts were regarded as independent risk factors for intracardiac thrombus in PPCM. A risk stratification model derived from these risk factors, which was economic and easily applicable in clinical practice, could rapidly and accurately identify PPCM patients with higher‐risk of intracardiac thrombus.